The Role of Some Dimensions of the Smart Organization in Enhancing Talent Management Processes : An analytical study of the the sample views of some Administrative leaders at private hospital in the Erbil City - Ahlam Ibrahim wali; Neewar Salahaddin Abdullah (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
The research aims to study the topic of some dimensions of the smart organization and its role in talent management. In order to verify these hypotheses, they were subjected to a set of statistical tests and the research adopted a descriptive and analytical approach. The results of the analysis revealed the existence of statistically significant differences between the respondents' responses towards the dimensions of the smart organization and the dimensions of talent management. According to the personal characteristics of respondents, that is, they have an equal or convergent view of both the dimensions of the smart organization and talent management. As for the research findings, the researcher suggested that attention should be paid to talent management by attracting talented people with outstanding skills.